2021
DOI: 10.1002/acn3.51416
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm dysfunction in severe COVID‐19 as determined by neuromuscular ultrasound

Abstract: Many survivors from severe coronavirus disease 2019 (COVID‐19) suffer from persistent dyspnea and fatigue long after resolution of the active infection. In a cohort of 21 consecutive severe post‐COVID‐19 survivors admitted to an inpatient rehabilitation hospital, 16 (76%) of them had at least one sonographic abnormality of diaphragm muscle structure or function. This corresponded to a significant reduction in diaphragm muscle contractility as represented by thickening ratio (muscle thickness at maximal inspira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 11 publications
(16 reference statements)
1
72
0
3
Order By: Relevance
“…Importantly, our neurophysiology findings opposed the differential diagnoses of critical illness neuropathy/myopathy, and 8 of 12 patients did not receive invasive mechanical ventilation. We therefore hypothesise that, in certain patients, SARS-CoV-2 directly infects the phrenic nerve or the diaphragm muscle (the former most likely given the hemi diaphragm elevation), agreeing with others 2–5. Recovery from such nerve injury takes time; Summerhill et al 10 found return of diaphragm function could take up to 3 years, with a mean recovery time of 14.9 months.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Importantly, our neurophysiology findings opposed the differential diagnoses of critical illness neuropathy/myopathy, and 8 of 12 patients did not receive invasive mechanical ventilation. We therefore hypothesise that, in certain patients, SARS-CoV-2 directly infects the phrenic nerve or the diaphragm muscle (the former most likely given the hemi diaphragm elevation), agreeing with others 2–5. Recovery from such nerve injury takes time; Summerhill et al 10 found return of diaphragm function could take up to 3 years, with a mean recovery time of 14.9 months.…”
Section: Discussionsupporting
confidence: 75%
“…Ultrasound has been used to measure diaphragm dysfunction during acute COVID-19 infection 3–5. Farr et al 4 studied 25 inpatients undergoing rehabilitation, having been ventilated for COVID-19 pneumonia. They found 80% had at least one structural or functional diaphragmatic abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 176 , 177 , 178 , 179 , 180 Farr et al. 184 reported that patients who required mechanical ventilation during COVID‐19 have a high prevalence of diaphragm dysfunction. They suggested that diaphragm dysfunction significantly contributes to dyspnoea in post‐COVID‐19 patients.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 99%
“…Respiratory sequelae have inevitably been shown to have repercussions at neuromuscular levels. In fact, dysfunctions of both respiratory and skeletal muscles have been described in about 40% of patients admitted to intensive care units, resulting in persistent symptoms of fatigue, weakness and shortness of breath [ 40 42 ]. Furthermore, it has been hypothesized that a direct muscle affection of SARS-CoV-2 may be responsible for structural alterations, even in patients who have had an apparently mild disease outcome [ 43 ].…”
Section: Clinical Manifestation Of Covid-19 and Post-acute (Long) Cov...mentioning
confidence: 99%